Understanding the Formation of Software as a Service (Saas) Commitment the Relational Value Creation Perspective - Chia-Shiang Hsu; Shih-Wei Chou (International Journal of Informatics and Information Systems, 2021)
This study focuses on the use of an important IT innovation--software-as-a-service (SaaS), and draw on sensemaking and the dedication-constraint framework to explain the formation of SaaS commitment. Building on and extending prior studies, we posit that managers’ perceived relational value from SaaS consumption transforms their initial sensemaking of SaaS features into commitment. SaaS features are characterized as strength frames and weakness frames. Perceived relational values are conceptualized as process flexibility, task-knowledge coordination, process specificity, and trust. The proposed model and hypotheses are largely supported by the empirical data from 169 SaaS client firms. We discuss theoretical and practical implications.